Under the bed - Bright, Paul.; Cort, Ben (London : Little Tiger Press, 2003)
An expedition under the bed reveals a variety of creatures--hairy green, spiny red, warty and winged--that are not scary, but they are all afraid of the newest arrival.
5.1
K-3
Keywords: Fear -- Fiction; Humorous stories; Monsters -- Fiction; Stories in rhyme; Fear -- Fiction; Humorous fiction; Monsters -- Fiction; Stories in rhyme